Childhood adversities and post-traumatic stress disorder: evidence for stress sensitisation in the World Mental Health Surveys. (November 2017) - McLaughlin, Katie A.; Koenen, Karestan C.; Bromet, Evelyn J.; Karam, Elie G.; Liu, Howard; Petukhova, Maria; Ruscio, Ayelet Meron; Sampson, Nancy A.; Stein, Dan J.; Aguilar-Gaxiola, Sergio; Alonso, Jordi; Borges, Guilherme; et al.
Abstract : Background: Although childhood adversities are known to predict increased risk of post-traumatic stress disorder (PTSD) after traumatic experiences, it is unclear whether this association varies by childhood adversity or traumatic experience types or by age. Aims: To examine variation in associations of childhood adversities with PTSD according to childhood adversity types, traumatic experience types and life-course stage. Method: Epidemiological data were analysed from the World Mental Health Surveys ( n = 27017). Results: Four childhood adversities (physical and sexual abuse, neglect, parent psychopathology) were associated with similarly increased odds of PTSD following traumatic experiences (odds ratio (OR)=1.8), whereas the other eight childhood adversities assessed did not predict PTSD. Childhood adversity–PTSD associations did not vary across traumatic experience types, but were stronger in childhood-adolescence and early-middle adulthood than later adulthood. Conclusions: Childhood adversities are differentially associated with PTSD, with the strongest associations in childhood-adolescence and early-middle adulthood. Consistency of associations across traumatic experience types suggests that childhood adversities are associated with generalised vulnerability to PTSD following traumatic experiences.